Study of optical modulation of the bipolar exposed transistor using semiconductor laser - Taghreed Younis; Musab Mohammed (College of Education for Pure Sciences, 2008)
Abstract: The effects of semiconductor laser light on static and dynamic characteristics of bipolar exposed transistor had been studied experimentally. There was no significant influence on these characteristics in the absence of semiconductor light on transistor device. Analog optical modulation of bipolar transistor had been realized with semiconductor laser light direct modulation, while there was evident effect of injection current of semiconductor laser on the harmonic of spectrum modulation of transistor output. Optical modulation of bipolar transistor had been realized using pulse width modulation technique, and there was no deformation in pulse shape out from collector of the transistor modulated by small duration time pulses. Deformation in pulse shape out of the bipolar transistor has been observed when semiconductor laser modulated by large duration time pulses that is decrease qualification of data transfer.